2023
DOI: 10.1097/ta.0000000000004040
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing combat readiness for military surgeons without trauma fellowship training: Engaging the “voluntary faculty” model

John Yonge,
Shaina Schaetzel,
Jessie Paull
et al.

Abstract: BACKGROUND Appropriate operative volume remains a critical component in mitigating surgical atrophy and maintaining clinical competency. The initiation of military-civilian surgical partnerships (MCPs) has been proposed for addressing knowledge, skills, and abilities (KSA) metrics to address concerns over operational readiness and the low acuity experienced by military surgeons. This study investigates the first partnership for Navy surgical staff at a nonacademic Military Treatment Facility (MTF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“… 2 3 8–10 26–28 Recent data suggest that these programs may be beneficial in helping military surgeons obtain the knowledge, skills, and abilities (KSA) thresholds that the Military Health System has adopted to assess for readiness deficits. 1–3 19 KSA metrics, which were designed to encompass the attributes required to be a proficient surgeon for critical wartime procedures, assign a point system to individual surgeon case volumes based on the level of complexity and scope of the procedure. 19 Although scores greater than 14,000 per year suggest that a military surgeon is ready to effectively deploy, recent data suggest that only roughly 10% of military surgeons are meeting the aforementioned threshold.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 2 3 8–10 26–28 Recent data suggest that these programs may be beneficial in helping military surgeons obtain the knowledge, skills, and abilities (KSA) thresholds that the Military Health System has adopted to assess for readiness deficits. 1–3 19 KSA metrics, which were designed to encompass the attributes required to be a proficient surgeon for critical wartime procedures, assign a point system to individual surgeon case volumes based on the level of complexity and scope of the procedure. 19 Although scores greater than 14,000 per year suggest that a military surgeon is ready to effectively deploy, recent data suggest that only roughly 10% of military surgeons are meeting the aforementioned threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study did not specifically assess the individual KSA values assigned to each surgeon, a multitude of recently published studies have addressed this at various MCPs and concluded that MCPs offer a feasible way to successfully increase individual KSA values to promote surgical readiness. 1–3 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations